2018
DOI: 10.6002/ect.2017.0293
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In intensive care units, differences in definitions and care of patients with brain death continue to be a complication. There has been a lack of progress in criterion standards of brain death diagnosis and donor care, as verified by our survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The health care professionals also felt that the BD diagnosis protocols provided by the Turkish Ministry of Health were unhelpful and in need of improvement if they were to contribute to improvements in organ donation rates. 17 The lack of official guidance on BD diagnosis may have contributed to the below-average organ donation rates in the present study. While the number of BD diagnoses was stable over time for some cities in our study, for others, it was not; for example, there was an apparent and unexplained decrease in the number of BD diagnoses made in the years 2013 and 2015 in Kayseri.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The health care professionals also felt that the BD diagnosis protocols provided by the Turkish Ministry of Health were unhelpful and in need of improvement if they were to contribute to improvements in organ donation rates. 17 The lack of official guidance on BD diagnosis may have contributed to the below-average organ donation rates in the present study. While the number of BD diagnoses was stable over time for some cities in our study, for others, it was not; for example, there was an apparent and unexplained decrease in the number of BD diagnoses made in the years 2013 and 2015 in Kayseri.…”
Section: Discussionmentioning
confidence: 76%
“…While organ donation coordinators, who have a key role in improving donation rates, are assigned by the Ministry of Health in Turkey, Sarıtaş et al reported that most health care professionals thought that doctors should take the role of organ donation coordinators. 17 Kayseri, a metropolitan city with over one million, had a high cadaveric organ donation rate in 2014, but no donations in 2012, 2013, or 2015 (►Fig. 3) were observed.…”
Section: Discussionmentioning
confidence: 99%
“…BD is also related to organ and tissue donation, a procedure that is a significant advancement in the treatment of diseases of renal, hepatic, cardiac, and pulmonary origin. However, globally, a difficulty faced with regard to transplants is the much greater demand than the supply of organs [5] and the underreporting of BD cases, from which most solid organs for transplantation originate [6].…”
Section: Introductionmentioning
confidence: 99%